Automated breast ultrasound: A comparison study with handheld ultrasound in detection and characterization of lesions in mammographically dense breast - Ahmed, Saja Ali; Joori, Salam M. (AL-Kindy College Medical Journal, 2022)
Background: Although mammography is a powerful screening tool in detection of early breast cancer, it is imperfect, particularly for women with dense breast, which have a higher risk to develop cancer and decrease the sensitivity of mammogram, Automated breast ultrasound is a recently introduced ultrasonography technique, developed with the purpose to standardize breast ultrasonography and overcome some limitations of handheld ultrasound, this study aims to evaluate the diagnostic efficacy of Automated breast ultrasound and compare it with handheld ultrasound in the detection and characterization of breast lesions in women with dense breasts. Objectives: To evaluate the diagnostic efficacy of Automated breast ultrasound and compare it with hand held ultrasound in detection and characterization of breast lesions in women with dense breast. Subjects and Methods: A prospective observational study conducted at Oncology Teaching Hospital during the period of ten months from 1st of February till 1st of December 2020. Included 62 women with dense breasts on diagnostic mammograms. All women underwent technician performed automated breast ultrasound and radiologist performed handheld ultrasound for both breasts. All suspicious lesions with selected probably benign lesions underwent biopsy, handheld ultrasound detected 48 masses (67.6%), 15 of them (21.1%) were cystic, automated breast ultrasound detected 54 masses (76.1%); 20 of them (28.2%) were cystic. The sensitivity of handheld ultrasound was=87.5%, Specificity=58.8%, the sensitivity of automated breast ultrasound was=93.8%, Specificity=70.6%. Conclusion: Automated breast ultrasound is an effective modality to detect occult breast lesion in women with dense breasts, automated breast ultrasound and handheld ultrasound have a reliable agreement in detection and characterization of breast lesions with higher accuracy of automated breast ultrasound in the evaluation of malignant lesions.